IMPACT OF COVID-19 PANDEMIC ON RUBBER FARMER HOUSEHOLD IN TANDING MARGA VILLAGE, PENUKAL ABAB LEMATANG ILIR REGENCY - Fetri Yanti; Desi Aryani; Dwi Wulan Sari; Henny Malini; Merynda Indriyani Syafutri (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Rubber prices in 2020 during the Covid-19 pandemic decreased in March, April, and May. The decline in rubber prices in the domestic market was caused by a decline in world rubber demand, this affected the selling price of rubber at the farmers’ level. The impact of the decline in rubber prices also affects the income of rubber farmers who depend on rubber farming for their lives. This condition affects in the decreasing of farmers' purchasing power for primary and secondary products. This study aimed to analyze the differences between income and household consumption expenditure of rubber farmers before and during the Covid-19 pandemic in Tanding Marga Village. The study used survey method. Data collection was carried out in March 2021. Sampling was done using the simple random sampling method. The total sample for the analysis tool was 41 rubber farmers from 474 total rubber farmers. The data processing method used a paired two-sample t-test analysis tools. The results showed that there were differences in the income and household consumption expenditure of rubber farmers before and during the Covid-19 pandemic. Farmers income decreased -12.61% during the Covid-19 pandemic. Income also affects consumption expenditures of farmer households. The household consumption expenditure decreased as much as -14.76% during the Covid-19 pandemic. Based on the results of the t-test, there are significant differences between farmer household consumption expenditures before and during the Covid-19 pandemic. Farmers should implement adaptation strategies to overcome the decline in income, which is by finding other income sources.